Imagine There Is War and It Is Tweeted Live – An Analysis of Digital Diplomacy in the Israeli-Palestinian Conflict - Kretschmer, Lisa-Maria (Global Media Journal - German Edition, 2017)
The interplay between use of force in conflicts and involved parties’ rhetorical efforts to determine related international discourse has long been subject of research and debate. However, how and why states adopt digital media in conflict, as well as how the emerging opportunity for “Digital Diplomacy” influences their actual communication warrants further consideration. This question raised in public, media and academia during Israel’s eight-day operation “Pillar of Defense” in Gaza in November 2012, when the military confrontation between Israel and Hamas was mirrored in a clash on social media as additional battlefield. The presented analysis of Israel’s online performance bases on Ben Mor’s self-presentation framework (2007, 2012), which explains constraints for structure and substance of communication by which states seek to build, maintain or defend their image in home and foreign audiences. Relevant Israeli Twitter feeds are analyzed and results flanked by semi-structured interviews with Israeli communication officials. Accordingly, Israel more than other political actors engages in proactive Digital Diplomacy, expecting benefits of directly reaching crucial publics and providing an alternative story, while accepting a certain loss of control. The constant communication aims at explaining and thus “humanizing” Israel’s militarized image in the Israeli-Palestinian conflict. However, with a focus on hard-power messages (threat scenarios, delegitimization, in-group/ out-group thinking, military instead of political successes) and the absence of political solutions, it is unlikely to convey a peace-oriented image or even – taking a longer view – to prepare the ground for a political solution.